2014
DOI: 10.1002/rra.2782
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate Community Responses to Annual Flow Variation from River Regulation: An 11‐Year Study

Abstract: The majority of the world's large river systems is affected by dams. The influences of unnatural regimes induced by flow management are wide-ranging from both biotic and abiotic standpoints. However, many of these effects are not evident over short (1-2 years) periods (e.g. impacts of annual flow variation). This study examines the long-term effects of annual flow variation on the macroinvertebrate community in the Chattahoochee River (GA) in the reaches below Buford Dam, the major water control structure on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 48 publications
2
10
0
1
Order By: Relevance
“…The presence of Lake Iseo, moreover, prevents the drift of lotic taxa from the upstream rivers to the investigated sites and indirectly provides the river with lentic taxa. Numerous lotic taxa appeared at just site 4 alone, the farthest from the lake, similar to the pattern reported by Holt et al [83] in the Chattahoochee River (Georgia, USA) where no EPT indicator taxa existed directly below the dam but increased with the distance downstream.…”
Section: Differences In the Similarity: Cross-site Comparisonsupporting
confidence: 86%
“…The presence of Lake Iseo, moreover, prevents the drift of lotic taxa from the upstream rivers to the investigated sites and indirectly provides the river with lentic taxa. Numerous lotic taxa appeared at just site 4 alone, the farthest from the lake, similar to the pattern reported by Holt et al [83] in the Chattahoochee River (Georgia, USA) where no EPT indicator taxa existed directly below the dam but increased with the distance downstream.…”
Section: Differences In the Similarity: Cross-site Comparisonsupporting
confidence: 86%
“…In the run mesohabitats, the genus Girardia, the second dominant group, was negatively affected by peak events occurring 30 days before the sampling date. A similar trend was observed at the Chattahoochee River in the southern Appalachian Mountains, where noninsect macroinvertebrates such as flatworms (Tricladida) were washed away during high flow events (Holt, Pfitzer, Scalley, Caldwell, & Batzer, 2015). Tomanová and Usseglio-Polatera (2007) report that the order Tricladida, to which the genus Giardia belongs, possesses low ability to adhere to the bottom materials of the streams despite FIGURE 4 Typical cross sections observed in pool, run, and riffle mesohabitats, showing levels of water surface under different discharge conditions, namely, large peak flow (LPF), small peak flow (SPF), low flow (LF), and median (M, observed in the period from 2011 to 2013).…”
Section: Key Hydrological Indicessupporting
confidence: 69%
“…76 km downstream from the dam) (Holt, Pfitzer, Scalley, Caldwell, Capece et al., ). Moreover, the dam is operated for hydropower; accordingly, previous studies reported extreme flow variation within a single day, with diel fluctuations of >1 order of magnitude being common (Holt, Pfitzer, Scalley, Caldwell, & Batzer, ; Holt, Pfitzer, Scalley, Caldwell, Capece et al., ). Since year 2000, the National Park Service has been monitoring aquatic macroinvertebrates in four sites downstream of Buford dam, along a continuous stretch of the Chattahoochee River located 1, 8, 28, and 45 river km below the dam.…”
Section: Methodsmentioning
confidence: 99%
“…Every 3 months over a period of 11 years (2001–2011), aquatic macroinvertebrates were collected using Surber samplers (500‐μm net) in each of the four studied sites. Three replicate samples covered each of the dominant microhabitats at the reach scale, and macroinvertebrates were preserved in 70% isopropyl and identified to the lowest possible taxonomic level (genus in most cases) in the lab (see Holt, Pfitzer, Scalley, Caldwell, & Batzer, ; Holt, Pfitzer, Scalley, Caldwell, Capece et al., for more details and identification keys). Abundance data from replicate samples were pooled to obtain a single sample per visit and site, and 35 taxa (after excluding taxa with <1% abundance) were retained for biological trait analyses.…”
Section: Methodsmentioning
confidence: 99%